DEVELOPMENT OF SURGICAL INSTRUMENTS FOR ROBOT- ASSISTED BIPORTAL ENDOSCOPIC SPINE SURGERY(BESS) - Karakoyun, Armanc; Seo, Hyeonseok; Han, HyungTaeg; Kim, Chunwoo (PROCEEDINGS OF THE 2022 DESIGN OF MEDICAL DEVICES CONFERENCE (DMD2022), 2022)
Robots are being widely used for minimally invasive surgery in various specialties. However, for minimally invasive spine surgery, the application of the robots has been limited to guidance of instrument placement. In this paper, as a part of the development of a tele-operated surgical robot for biportal endoscopic spine surgery, we present the development of robotized instruments for tissue removal. Surgical punch, pituitary and shaver, the instruments most widely used for bone and tendon removal in spine surgery, is modified for the surgical robot. Spine bone-breaking experiments have been conducted for the identification of design parameters and the resulting designs have been reported. Additionally, a prototype has been manufactured for each instrument.